1999
DOI: 10.1103/physrevd.59.044018
|View full text |Cite
|
Sign up to set email alerts
|

Physical nature of the central singularity in spherical collapse

Abstract: We examine here the nature of the central singularity forming in the spherically symmetric collapse of a dust cloud and it is shown that this is always a strong curvature singularity where gravitational tidal forces diverge powerfully. An important consequence is that the nature of the naked singularity forming in the dust collapse turns out to be stable against the perturbations in the initial data from which the collapse commences.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 17 publications
3
57
0
Order By: Relevance
“…This fact was already shown by Deshingkar, Joshi and Dwivedi (1999). This can be confirmed by the result of Sec.…”
Section: Examples a Dust Collapsesupporting
confidence: 81%
See 1 more Smart Citation
“…This fact was already shown by Deshingkar, Joshi and Dwivedi (1999). This can be confirmed by the result of Sec.…”
Section: Examples a Dust Collapsesupporting
confidence: 81%
“…It is important that the strength of the singularity is determined by the curvature divergence not only on the null geodesic but also on the timelike geodesic. Recently, Deshingkar, Joshi and Dwivedi (1999) showed that both SCC and LFC are satisfied for the timelike geodesics which terminate at the shell-focusing singularity.…”
Section: Introductionmentioning
confidence: 99%
“…The singularity satisfies not the strong curvature condition (SCC) defined by Tipler [32] but only the limiting focusing condition (LFC) defined by Królak [33] for radial null geodesics which terminate at the singularity. On the other hand, the singularity satisfies both LFC and SCC for radial timelike geodesics [21].…”
Section: Lemaître-tolman-bondi Solutionmentioning
confidence: 99%
“…For the C ∞ case, the redshift is finite and the naked singularity is not very strong. See [21][22][23] for details. Though the Einstein equation does not require such strong differentiability to initial data, we usually set such initial data in most astrophysical numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of singularity is an important issue because there have been attempts to relate it to stability [14]. A singularity is termed gravitationally strong or simply strong, if it destroys by crushing or stretching any object which falls in to it.…”
mentioning
confidence: 99%